HUBUNGAN PERAKARAN BEBERAPA KULTIVAR KEDELAI DENGAN KEMAMPUAN BERSAING MELAWAN GULMA - Doni Hariandi; Didik Indradewa; Prapto Yudono (Jurnal Agroekoteknologi, 2018)
ABSTRACTThe research was aimed to see the influence and rooting relationship to the ability of several cultivars of soybean to weed. This research was arranged using split plot design with three blocks as the repetition where the main plot was the weed treatments and those were weedy, weeding in a critical period, and weed-free. Sub-plot was the soybean cultivars which are Anjarmoro, Argomulyo, Burangrang, Gema, Gepakkuning, Kaba, and Wilis.The results showed that rooting variables that could be used as a marker of the ability of soybean plants to compete to weeds were root length and root volume.Keywords: competitive, cultivar, root, soy bean, weed